Indigenous Archaeology Through Consent, Consensus, and Collaboration - Aguilar, Danny Sosa (American Indian quarterly, 2024)
This article examines the important role Indigenous archaeology plays in developing collaborative partnerships that practice the principles of consent, consensus, and collaboration in archaeological projects such as the Abiquiú Mesa Project (AMP) in Abiquiú, New Mexico. In the Society for American Archaeology's Principles of Archaeological Ethics, the phrase "informed consent" is not defined, and the word "consensus" is not found. As more projects like AMP collaborate with Native American communities, defining the concepts of consent, consensus, and collaboration is crucial when conducting collaborative projects that incorporate Native American voices and perspectives. In AMP, consent is achieved through communication, voluntary participation, and capacity. Consensus in AMP considers the local context and the distinct levels of agreement by all community partners. Last, collaboration serves to build capacity, develop reciprocity, and incorporate Native American community knowledge. Rethinking archaeology with these principles acknowledges historical narratives and knowledge-producing methods that include the voices of the people whose history we study while stepping toward decolonizing the practice of archaeology.